ANALYSIS OF PRESUPPOSITION TRIGGERS FOUND IN THE UTTERANCES PRODUCED BY JAMES BOND CHARACTER IN DR. NO MOVIE - PRASTYA, DAVIT (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Presupposition, Presupposition Triggers, MovieThis study is about presupposition on utterances of  James Bond character in Dr. No movie. There is one problem to be solved the study, namely: What are the triggers of presuppositions of the main character’s speech in the James Bond movie “Dr. No”? The objective is to identify the triggers of presuppositions of the main character’s speech in the James Bond movie “Dr. No”.The research is a qualitative research. Descriptive study in textual analysisis applied in this study to analyze the presupposition triggers of the utterancesproduced by the main character script of Dr. No movie.The results  of the study reveal  that  ten  out  of thirteen  presupposition triggers are applied in the utterances of James Bond. The presupposition triggers are (a) definite descriptions, (b) change of state verbs, (c) iteratives, (d) verbs of judging, (e) temporal clauses, (f) cleft sentence, (g) implicit cleft with stressed continuents, (h) comparison and contrast, (i) non-restrictive relative clauses, (j) counterfactual conditionals and (k) questions. The writer found that James Bond produced 93 utterances which are containing presupposition triggers from 368 utterances uttered by James Bond. Questions are the most frequently used presupposition triggers (59 presupposition triggers) because as a secret service agent of British government, question is used by James Bond to interrogate people. Five most rarely used triggers were iteratives, verbs of judging, cleft sentence, non-restrictive relative clauses and counterfactual conditionals (1 presupposition trigger for each type) because as a secret agent, he did not really use these triggers to investigate something. The triggers that were not used by James Bond were factive verbs and implicature verbs.The writer suggests that the readers use presupposition triggers to presuppose utterances especially in the daily life. He also suggests that the next researchers, who want to conduct the study in the same topic, use theory fromanother theorist of presupposition and also use another object.